2020
DOI: 10.14260/jemds/2020/90
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Surgically Managed Diaphyseal Fractures in Children- A Prospective Study

Abstract: BACKGROUND Childhood injuries have become a global public health concern. It is estimated that 10-25 % of paediatric injuries are fractures. The definitive treatment of paediatric diaphyseal fractures has always remained controversial and determined by surgical experience and local trends of practice. The aim of this study was to study the outcome of surgically managed diaphyseal fractures in children. METHODS A prospective interventional study was done comprising of 42 fractures in 28 children having displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In their study, Reddy and Dhaniwala found that among the 28 cases, the most common mode of injury was a fall while playing in 18 cases. Additionally, five cases were attributed to road traffic accidents, three to falls from height, one to blunt trauma, and one to another cause [ 25 ]. Bandyopadhyay observed that among the 49 patients' domestic falls in 27 cases, road traffic accidents in 10 cases, sports injuries in seven cases, and falls from bicycle in five cases [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In their study, Reddy and Dhaniwala found that among the 28 cases, the most common mode of injury was a fall while playing in 18 cases. Additionally, five cases were attributed to road traffic accidents, three to falls from height, one to blunt trauma, and one to another cause [ 25 ]. Bandyopadhyay observed that among the 49 patients' domestic falls in 27 cases, road traffic accidents in 10 cases, sports injuries in seven cases, and falls from bicycle in five cases [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their investigation of 30 patients with diaphyseal fractures of long bones, Baig et al found that 17 (56.7%) of the patients had femoral fractures, seven (23.3%) had tibial fractures, one (3.3%) had humeral fractures, and five (16.6%) had forearm fractures [ 11 ]. In their other investigations, Reddy and Dhaniwala found that long bones other than the femur were frequently affected [ 25 ]. In their investigation of long bone fractures, Furlan et al noted 35 tibial, 42 forearm, 41 femoral, and 55 humeral fractures [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations